HAK WARIS JANDA DALAM PERKAWINAN YANG TIDAK MEMILIKI KETURUNAN (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR PERKARA 73K/AG/2015) - ABI YOGA HARAHAP (PREMISE LAW JURNAL, 2016)
According to the Islamic Law, a widow is an heir to her husband and receives a particular part of the inheritance because she is included into the group of people who has the right to inherit called Dzul fara-idh (the heirs whose part is specifically determined). Practically, the widow is often left alone without any descendant after her husband passes away; this was what happened in the case number 73K/AG/2015 that was taken for analysis. The research problem was how a widow without any descendant was positioned in her husband’s inheritance distribution according to the Islamic Law, how much her part was in accordance with the Islamic Law, and how the judge’s legal consideration was in handing out the Ruling of the Supreme Court on the Case Number 73K/AG/2015 in the Islamic Law. Keywords : Inheritance Right, Widow, Without Descendant